To study the relationship between factors of technostress creators and employees' job satisfaction at Telekom Malaysia Sentul / Nurlina Khairul Anuar - Anuar, Nurlina Khairul (Faculty of Business and Management, 2013)
The purpose of this research is to study the relationship between factors of technostress creators and employees' job satisfaction in Telekom Malaysia Sentul at Kuala Lumpur. Moreover, this study was to determine the relationship technostress employee with their job satisfaction and to identify the factors that cause these employees are afraid or anxiety of the current technology. In getting relevant data, 123 qestionnaires were distributed to the employees in Telekom Malaysia Sentul at Kuala Lumpur. The respondents are chosen as convenience sampling in administration department. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. The analysis includes frequency, reliability, mean and standard deviation and also correlation analysis. The finding showed significance relationship between technostress creators and employees' job satisfaction in administration department. Thus, recommendations are included in this project paper in order to help that organization can reduce anxiety employees with the current technology to improve the employees' skill and development and more faster to doing their work by using new technology system in the organization.